The Effect of Leadership Style and Entrepreneurship Orientation on the Performance of Village Owned Business Entities (BUMDes) in Bengkalis Regency - Velia Ayu Sasqia (LPPM Universitas Terbuka, 2022)
Village-Owned organisations (BUMDes) are one of the efforts to expand the village economy. BUMDes are set up on the basis of the wishes and capability of the village as an attempt to enhance the welfare of the network community. therefore, it is very important in an effort to make sure the achievement of BUMDes with the intention to gain superior overall performance. This look at goals to decide the impact of leadership style and entrepreneurial orientation on the performance of BUMDes in Bengkalis Regency. facts became accrued the usage of a questionnaire dispensed to the BUMDes director, BUMDes secretary or treasurer and BUMDes supervisors. Data was amassed with the aid of distributing questionnaires given to 303 respondents, however most effective 261 (86.14%) of respondents filled out the questionnaire completely and can be processed. The analytical device used is multiple linear regression analysis the usage of SPSS version 23. This observe uses quantitative statistics. The supply of data used in this study is primary statistics and data series is carried out directly using a questionnaire that is measured using a Likert scale. The outcomes of this examine suggest that the variables of management style, and entrepreneurial orientation have an effect at the overall performance of BUMDes.